Bible translation as 'ideological text production' - with special reference to the cultural factor and Psalm 137 in Chichewa - Wendland, Ernst R. (Old Testament Essays, 2004)
My investigation relates the topic of 'ideological text production' more specifically to the practice of Bible translation within a particular social and cultural setting, namely, that of south-central Africa. This case study is necessarily quite selective in nature and focused upon the text of Psalm 137 both in the original Hebrew and also, via translation, in the Chichewa language. The ideology of any human language is shaped by the total culture of the people who speak it, while that of a given text is also influenced by the communicative goals of its author in relation to an envisaged readership within a given context of reception and use. Similarly, the ideology of a certain translation is motivated by the explicit or unstated objectives of those who commission and oversee it. This includes the particular translational method that they have adopted to accomplish their aims in relation to their primary target audience and socio-cultural milieu. The purpose of this paper is to call attention to some of these significant ideological factors and to suggest how important a coordinated communal approach is to the achievement of a translation committee's chosen set of goals. Various aspects of this subject and the salient issues involved are illustrated with reference to the communication of Psalm 137 in Chichewa.
free